The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1103/physreva.96.062503
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic analysis of the Berry curvature in theEeJahn-Teller model

Abstract: The effective Hamiltonian for the linear E ⊗ e Jahn-Teller model describes the coupling between two electronic states and two vibrational modes in molecules or bulk crystal impurities. While in the Born-Oppenheimer approximation the Berry curvature has a delta function singularity at the conical intersection of the potential energy surfaces, the exact Berry curvature is a smooth peaked function. Numerical calculations revealed that the characteristic width of the peak is K 1/2 /gM 1/2 , where M is the mass ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 69 publications
(109 reference statements)
5
32
0
Order By: Relevance
“…On the other hand, a nonzero value of Planck's constant (no matter how small) leads to regular nuclear trajectories evolving under the influence of smoothened effective potentials given by the convolution of the original potentials with the nuclear probability density. In turn, the removal of the singularities makes the Berry phase a geometric (path-dependent) quantity in analogy with the recent findings in [44,43]. As we shall see in the simple case of Jahn-Teller systems, the geometric phase resulting from the Bohmian closure successfully reproduces the phenomenology appearing in exact nonadiabatic studies [43]: starting from zero, the Berry phase rapidly tends to the Aharonov-Bohm topological index as the loop encircling the conical intersection becomes distant from the singularity.…”
Section: Goal Of the Papersupporting
confidence: 75%
See 3 more Smart Citations
“…On the other hand, a nonzero value of Planck's constant (no matter how small) leads to regular nuclear trajectories evolving under the influence of smoothened effective potentials given by the convolution of the original potentials with the nuclear probability density. In turn, the removal of the singularities makes the Berry phase a geometric (path-dependent) quantity in analogy with the recent findings in [44,43]. As we shall see in the simple case of Jahn-Teller systems, the geometric phase resulting from the Bohmian closure successfully reproduces the phenomenology appearing in exact nonadiabatic studies [43]: starting from zero, the Berry phase rapidly tends to the Aharonov-Bohm topological index as the loop encircling the conical intersection becomes distant from the singularity.…”
Section: Goal Of the Papersupporting
confidence: 75%
“…has an intrinsic topological nature and it is actually expressed as a topological index. While this topological character is well established in the standard Aharonov-Bohm effect [3], its manifestation has recently been debated in [39,44,43]. Therein, Gross and collaborators have shown that the molecular Berry phase may be considered as a manifestation of a geometric (path-dependent) effect.…”
Section: Generalized Born-oppenheimer Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This study was the first detailed analysis in the time domain of the properties of the EF in connection to CIs. (The EF can also be performed in the time-independent picture [28][29][30][31][32][33][34][35], and analyses of CI in this framework were also proposed [36][37][38][39]. )…”
Section: Introductionmentioning
confidence: 99%